(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article discusses the existing legal framework, standards and norms of wastewater treatment in the design and construction of wastewater treatment systems in the settlements of the country. Due to the exceeding of service life and lack of capital investments, sewage networks and wastewater treatment facilities are in a state requiring rehabilitation or new construction. The existing sewage treatment plants of cities provide for the reuse of treated wastewater for irrigation of agricultural land. The current standards of the Kyrgyz Republic generally comply with international standards, except for the concentration of ammonium in water discharged for irrigation purposes.